2015
DOI: 10.1080/14681811.2015.1080158
|View full text |Cite
|
Sign up to set email alerts
|

‘Everywhere they say that it’s harmful but they don’t say how, so I’m asking here’: young people, pornography and negotiations with notions of risk and harm

Abstract: In Finland, as elsewhere in Western countries, public debate about the dangers of pornography and the sexual practices of adolescents has taken on new urgency due to wider Internet access and the development of smart phones. Over the past decade, there have been reports that Finnish young people are being harmed, traumatised and sexualised by the media. The consumption of pornography by minors has, for example, been associated with visual harassment and visual violence in terms of the harmful effects it is see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 17 publications
3
20
0
4
Order By: Relevance
“…This is consistent with research that suggests that young people have an interest in sexuality and respond best to environments that encourage trust and openness and rely on evidence rather than moralistic undertones [26]. However, relying solely on evidence is challenging when dealing with emerging public health issues such as online pornography, where evidence is still being developed [7]. Our results suggest that this may be overcome by providing young people with the best available information, including on why there is lack a of consensus in evidence, and providing opposing views and discussion points to help them make their own informed decisions.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This is consistent with research that suggests that young people have an interest in sexuality and respond best to environments that encourage trust and openness and rely on evidence rather than moralistic undertones [26]. However, relying solely on evidence is challenging when dealing with emerging public health issues such as online pornography, where evidence is still being developed [7]. Our results suggest that this may be overcome by providing young people with the best available information, including on why there is lack a of consensus in evidence, and providing opposing views and discussion points to help them make their own informed decisions.…”
Section: Discussionsupporting
confidence: 77%
“…For example, a large (n=4564) survey of young people aged 14 to 17 years found that boys who regularly watch online pornography were significantly more likely to express negative gender attitudes [5]. Studies are yet to describe the direction or strength of these associations to be able to identify a causal relationship between pornography and harm [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Concerns over the impact of different kinds of media content on young people are critically examined in order to go beyond the dominant presumptions about the supposed ill effects of sexual media (see for example Attwood et al., 2018; Buckingham and Bragg, 2004; Knudsen et al., 2007; Mulholland, 2013; Nielsen et al., 2015; Spišák, 2016, 2017; Spišák and Paasonen, 2016; Tsaliki, 2011, 2015, 2016). For example, Buckingham and Bragg (2004) conducted the first systematic account within cultural studies about children's understandings of sex, intimacy and sexuality concerning media.…”
Section: Public Debate On Pornography and The Perspective Of Girlsmentioning
confidence: 99%
“…While the cultural role and status of pornography have been intensely debated in the course of the 2000s, there are tensions in identifying its various, allegedly mainly adverse, outcomes, causes and effects. Furthermore, these debates mostly lack the perspective of young people (Attwood et al., 2018; Buckingham and Chronaki, 2014: 305; Spišák, 2016, 2017; Tsaliki, 2016). This shortcoming is noteworthy, given how the young are considered as being at particular risk due to online pornography.…”
Section: Public Debate On Pornography and The Perspective Of Girlsmentioning
confidence: 99%
“…W dyskusji na temat oddziaływania tego typu materiałów na młodzież można spotkać się z opinią, że temat szkodliwości tej sfery internetowej stał się wyolbrzymiony (Spišák, 2016). Istnieją koncepcje, w ramach których zakłada się, że ze względu na łatwą dostępność materiałów pornograficznych oraz nakładającej się na ten fakt specyfiki wieku dojrzewania, związanej z odkrywaniem własnej seksualności, poszukiwanie filmów, zdjęć zawierających tło seksualne jest naturalnym elementem procesu rozwojowego (Naezer, 2018).…”
Section: Dyskusjaunclassified